War and religion:: How pre-modern configurations explain some aspects of recent and current warfare - Buc, Philippe (Skript Historisch Tijdschrift, 2025)
Knowledge of the pre-modern religious past allows one to understand facets of modern war that do not seem to have their place in Modernity. Three contemporary examples, the Islamist terror group Daesh, America’s George Walker Bush at war in 2001–2003, and the Russian Orthodox Patriarch of Moscow, will illustrate this point.